An Experience of Using Cyclosporin 0.05 % (Restasis) in Conjunctival Lymphangiectosia Treatment of Patients With Dry Eye Syndrome - S. A. Volik; S. I. Isaenko (Российский офтальмологический журнал)
Two clinical cases of lymphangiectosia treatment using cyclosporine 0.05 % (Restasis) in female patients with moderate dry eye syndrome (DES) are presented. Apart from DES, the patients had lymphangiectosia of bulbar conjunctiva that caused constant feeling of a foreign body in the eye and complaints about a cosmetic defect. In case 1, there was a single cyst, and in case 2, a large cyst with multiple small cysts. Both patients were prescribed cyclosporin emulsion 0.05 % (Restasis) to treat DES. In case 1, the cyst regressed completely in four weeks. In case 2, all small cysts regressed while the remaining large cyst was punctuated in aseptic conditions by an insulin needle. The treatment with cyclosporin 0.05 % was continued // Russian Ophthalmological Journal, 2016; 1: 84-86.